IMPLEMENTATION OF ARTICLE 33 OF THE 1945 CONSTITUTION BY STRENGTHENING THE STATE-OWNED ENTERPRISES (SOE) IN THE PERSPECTIVE OF FOREIGN INVESTMENT AND INTERNATIONAL PRIVATE LAW - Barata, Fausta Ari; Octora, Theresye Yoanyta; Heliaantoro, , (Wijaya Putra Law Review, 2024)
Associated with one of the objectives of the law, which is to provide benefits to many people, so with the enactment of Law No. 1 of 1967 concerning Foreign Investment, it also provides great benefits for the host country in providing employment opportunities for the community, doubling the power in the local economy, providing residue in both equipment and technology transfer, providing a way or marketing path that can be traced by local entrepreneurs for exported products while still contributing instant foreign exchange and taxes to the country, more resistant to fluctuations in interest and foreign exchange, and providing protection regional politics and security because if the investors come from strong countries, security assistance will also be provided. Liberalization in the investment sector, especially foreign investment, basically existed long before the enactment of the Law No. 25 of 2007 concerning Investment, it also appeared implicitly in several laws and regulations in Indonesia, include Law No. 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition, Law No. 22 of 2001 concerning Oil and Natural Gas, and Law No. 30 of 2009 concerning Electricity. The many liberal laws and regulations described above indicate that the right to control by the state concerning the livelihoods of the people as amended by the 1945 Constitution is "castrated" by laws that are not in harmony with it. In fact, Law No. 25 of 2007 concerning Investment was issued in the framework of implementing the mandate of Article 33 of the 1945 Constitution. Thus, the opening of foreign investment in production sectors that dominate the livelihoods of many people is certainly contrary to the concept of the right to control by the state as stipulated in Article 33 of the 1945 Constitution.